Digital participation: category conceptualization in foreign practice of civic engagement - S. B. Abramova (Цифровая социология)
The participatory model of civic participation is attracting more and more attention from researchers of modern societies. The article is devoted to the issue of determining the content and structural components of digital participation concept. The problem of the digital technologies’ effectiveness for the implementation of civic activity is considered in the context of the practice and experience of foreign organizations in the implementation of digital activism. The author conducts an informal analysis of 46 foreign websites, their content is related to the development of digital participation (government agencies, educational and charitable organizations, digital platforms). The study made it possible to build a structural model of digital participation, including the main subjects, their goals and the necessary conditions / factors of the non-digital and digital environment, as well as the personal component. This is connected with an expanded context in the interpretation of digital participation, which considers the activities of not only the subjects of civic participation itself, but also all other subjects and conditions necessary for the involvement of citizens in digital participation. It is shown that the practice-oriented understanding of digital participation is based on a number of provisions in the documents of international organizations (the United Nations, the European Union) and is based on the assessment through various international indices. The participatory interpretation allows us to conclude that civic participation is extremely positive, based on a culture of participation and consistency in the goals of various social groups and subjects.